1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Mean value theorm [HARD]

  1. Jul 25, 2007 #1


    User Avatar
    Gold Member

    1. The problem statement, all variables and given/known data
    f is a continues function in [a,b] and has a second derivative in (a,b). L(x) is a line that goes through (a,f(a)) and (b,f(b)).
    Prove that if f''(x)>0 in (a,b) then L(x)>f(x) for every x in (a,b)

    2. Relevant equations


    3. The attempt at a solution

    First of all,
    [tex] L(x) = f(a) + \frac{f(b)-f(a)}{b-a} (x-a) [/tex]
    and so
    [tex] L(x) - f(x) = f(a) - f(x) + \frac{f(b)-f(a)}{b-a} (x-a) [/tex]
    [tex] \frac{f(b)-f(a)}{b-a} = f'(t) [/tex] where t is in (a,b)
    and so
    [tex] ( L - f)' (x) = f'(t) - f'(x) [/tex]
    Now, [tex] ( L - f )' (x) = 0 [/tex] only when [tex] f'(t) = f'(x) [/tex]
    And since f''(x)>0 f'(x) is an injective function in (a,b) and so [tex] f'(t) = f'(x) [/tex] only when x=t. and since f''(x)>0 we get a maximum at x=t.
    Now, (L-f)(a) = 0 and (L-f)(b) = 0. If for any other x_0 =/= t
    (L-f)(x_0)=0 then that would mean that for some x in (a,x_0) and for some x in (x_0,b) (L-f)'(x) = 0, but this is impossible as (L-f)'(x) is injective and we alredy found one point (t) where (L-f)'(x) = 0.
    Also, (L-f)(t) > (L-f)(a) = 0 because it's a maximum in (a,b). And so for all x in (a,b) L-f)(x) > 0 => L(x) > f(x).

    I felt that that proof was pretty weak, especially towards the end. How can I make it better. And is there any easier way?
  2. jcsd
  3. Jul 25, 2007 #2


    User Avatar
    Homework Helper

    Hint (hopefully): Let f : I --> R be differentiable twice on an open real interval I. f is a convex function on I iff f''(x) >= 0, for every x in I.
  4. Jul 25, 2007 #3
    This is a proof that f is a convex function. As far as I know, the only way to do it is with a contradiction. Suppose there exists a t in (a,b) with [itex]L(t) \le f(t)[/itex]. That ought to make it feel more cleaner and mathy-like.

    Your logic is backwards, you're presupposing (L-f)'(x)=0 for some x. It makes more sense that since (L-f)(a)=0 and (L-f)(b)=0 that there would exist a t in (a,b) such that (L-f)'(t)=0.

    "and since f''(x)>0 we get a maximum at x=t." If g'(x)=0 and g''(x)<0 then g(x) is a local maximum. (L-f)'(t)=0 and f''(x)>0 doesn't tell you 'something gets maximized' (I'm not sure what you're saying gets maximized).

    Anyhow, since (L-f)''(x)=-f(x)<0 (L-f)(t) is a local maximum.
    Last edited: Jul 25, 2007
  5. Jul 25, 2007 #4
    Unfortunately that's not a hint. That's precisely the inference he's been asked to show.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook